An electro-optically tunable arrayed waveguide grating fabricated on thin film lithium niobate - Zhe Wang; Zhiwei Fang; Yiran Zhu; Jian Liu; Lang Gao; Jianping Yu; Haisu Zhang; Min Wang; Ya Cheng (APL Photonics)
We design and fabricate an eight-channel thin-film lithium niobate (TFLN) arrayed-waveguide grating (AWG) and demonstrate the electro-optical tunability of the device. The monolithically integrated microelectrodes are designed for waveguide phase modulation and wavelength tuning. Experiments show that the fabricated electro-optically controlled TFLN AWG has a channel spacing of 200 GHz and a wavelength tuning efficiency of 10 pm/V.